Carbon characteristics and the effect of terrain and cultivation on topsoil carbon and salts of the West Coast heuweltjies - Sakala, Brian Josat (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.